2020
DOI: 10.1055/a-1018-1902
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting MicroRNA-497 Improves the Effects of Exercise Training on Myocardial Infarction

Abstract: Exercise training (ET) could improve myocardial infarction (MI), and microRNA-497 is highly associated with MI. This study aimed to investigate whether the regulation of miR-497 is involved in the positive effects of ET on MI. MI rat models induced by left anterior descending (LAD) were subjected to interval training and infarct size was observed. Blood and myocardial samples were collected from the rats for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Previous studies indicated that the level of cardiac troponin I, a biomarker of MI, was significantly positively correlated with the content of miR-497 in the serum [ 23 ]. Meanwhile, it was reported that exercise training could improve the cardiac function through suppressing the expression of miR-497 in the heart tissues after MI [ 24 ]. Our data suggested that overexpression of miR-497 could aggravate the cardiac function damage after MI, which is in line with previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the level of cardiac troponin I, a biomarker of MI, was significantly positively correlated with the content of miR-497 in the serum [ 23 ]. Meanwhile, it was reported that exercise training could improve the cardiac function through suppressing the expression of miR-497 in the heart tissues after MI [ 24 ]. Our data suggested that overexpression of miR-497 could aggravate the cardiac function damage after MI, which is in line with previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a set of cardiac miRNAs in response to exercise with cardio-protective roles to regulate cell proliferation, metabolism, and apoptosis has been reported [ 38 , 39 , 40 ] (Table 1 , Ref. [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]). In response to physical exercise, these exercise-driven miRNAs have important roles in regulating exercise adaptation and could be used as promising therapeutic intervention.…”
Section: Exercise-responsive Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%
“…ET could reduce miRNA-497-5p expression under physiological and under MI pathological conditions. A miRNA-497-5p antagomir (inhibitor) could mimic the benefits of exercise on MI, including reduced infarct size and improved cardiac function, whereas miRNA-497-5p agomir aggravated the infarct size post-MI and abrogated the positive effects of ET maybe through its target chloride voltage-gated channel 3 ( CLCN3 ) [ 47 ]. Through a plasma miRNA profiling assay, miR-1192 was found to be increased by a four-week swim training.…”
Section: The Function Of Exercise-induced Mirnas In Myocardial Infarc...mentioning
confidence: 99%